Pengaruh Digital dan Word of Mouth Marketing Terhadap Popularitas Brand Awareness pada Bisnis Kopi Keliling di Surabaya - Filipe Ximenes Guterres; Kevin Denandra Budianto; Ivan Aubrey Adianto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
Digital marketing has become a new paradigm that defines marketing strategies, especially in the context of mobile coffee businesses. In this context, digital marketing involves the use of online platforms, social media, and digital technology to increase the visibility and appeal of mobile coffee. This analysis includes aspects such as consumer appeal, problems that occur, and trends that are happening among the people of Surabaya. With the significant growth of mobile device usage, the digital marketing strategy for mobile coffee includes mobile apps, online ordering, and e-payment to provide convenience to customers. This research provides an in-depth insight into how digital marketing can be a growth catalyst for mobile coffee businesses, enabling them to not only survive in this digital era but also thrive in the face of ever-changing market dynamics. Key words : Digital marketing, mobile coffee, trend.